Computers for schools team: helping everybody win. - Soonachan, Irwin (Corrections Today, 2000)
Part of a special section profiling outstanding members of the corrections profession. The writer discusses the work of Computers for Schools instructor Brian Flynn with the inmates at the Massachusetts Correctional Institution-Shirley, a medium-security male facility. He explains that the inmates are given old computers to refurbish and that the computers are then sent to schools across the state. He outlines how this process works, Flynn's work, and why everyone involved stands to win from this program.